Spermatic Cord Sarcoma: A 20-Year Single-Institution Experience - Iafrate, Massimo; Motterle, Giovanni; Zaborra, Carlotta; Leone, Niccolò; Prayer-Galetti, Tommaso; Zattoni, Filiberto; Guttilla, Andrea; Cappellesso, Rocco; Dei Tos, Angelo Paolo; Rossi, Carlo Riccardo; Del Fiore, Paolo; Rastrelli, Marco; et al. (Frontiers in Surgery, 2020)
Introductionː Spermatic cord sarcomas represent a rare genitourinary malignancy with a challenging diagnostic and therapeutic pathway. Different histotypes have been described and prognostic factors remain poorly defined due to the paucity of data presented in literature. Methodsː Retrospective chart review of 22 adult patients treated for spermatic cord sarcoma in a single institution in the last twenty years was performed. Clinicopathological characteristics of the tumors were collected with primary and subsequent treatment. Survival analysis was performed in order to identify prognostic factors of disease specific survival. ResultsːThe median age at diagnosis was 68 years (58-78), the most common histotype was liposarcoma (14/22) and most patients (63.6%) were found to have positive surgical margins after surgery. The 5-year cancer specific survival was 91.3%. Grading (p=0.48); histotype (p=0.327) and type of intervention (p=0.732) were not associated with survival. All patients dead of disease had positive surgical margins (p=0.172). Conclusionː We report a good prognosis at 5 years. Accurate surgical resection remains the first and probably the most important step thus, according also to literature, negative surgical margins should be aimed.